Electrochemical energy storage devices and supercapacitors : an overview - Arote, Sandeep A. (IOP (Series). Release 21., 2021)
This book provides a comprehensive account of the fundamental aspects of electrochemical energy storage devices, with a focus on electrochemical supercapacitors. Building from an in-depth knowledge of the present state of energy utilisation, contextualised against the requirement for renewable energy, the book sets out the components and performance-governing parameters of conventional and supercapacitors, identifying the challenges, trends and limitations involved in their implementation.